PERAN ANGGARAN FLEKSIBEL DALAM PENGENDALIAN DAN ANALISIS BIAYA OVERHEAD PABRIK - Tuti Sriwedari; Lasria Sitorus; Jelita Febrianti Tampubolon; Ariel Immanuel Panjaitan; Robin Cornelius Siahaan; Nurlila Azmi Hutapea (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2026)
Budgets are a key tool in a company's financial planning and control process. However, in a dynamic business environment, fixed budgets are often unable to adjust to changes in production volume and economic conditions. Therefore, flexible budgets are a more adaptive solution because they can be adjusted to the company's actual activity level. This study aims to analyze in depth the role of flexible budgets in controlling and analyzing factory overhead costs. The research method used is a literature study by reviewing various relevant theories, books, and journals. The results of the study indicate that flexible budgets play a significant role in increasing the effectiveness of cost control, especially factory overhead costs, by providing more accurate information on cost deviations and operational efficiency. Furthermore, flexible budgets support variance analysis, allowing management to identify the causes of cost differences, whether due to changes in activity levels or inefficiencies. Thus, the implementation of flexible budgets can be a strategic tool for management in improving a company's financial performance and competitiveness in the manufacturing industry.